A head‐to‐head comparison of plasma phosphorylated tau assays in the real‐world memory clinic. (20th December 2022) - Suárez‐Calvet, Marc; Ashton, Nicholas J.; Puig‐Pijoan, Albert; Milà‐Alomà, Marta; Fernández‐Lebrero, Aida; García‐Escobar, Greta; González‐Ortiz, Fernándo; Kac, Przemyslaw Radoslaw; Brum, Wagner Scheeren; Benedet, Andréa Lessa; Rodriguez, Juan Lantero; Day, Theresa A.; et al.
Abstract: Background: Several blood phosphorylated tau (P‐tau) species (P‐tau181, P‐tau217, and P‐tau231) have shown high accuracy to detect AD pathology, but a direct comparison of the main blood P‐tau assays in a real‐world memory clinic is needed. The main aim of this study is to perform a head‐to‐head comparison of 9 plasma Tau assays and determine their accuracy to discriminate between symptomatic AD from non‐AD. Method: This is an observational and cross‐sectional study in the BIODEGMAR cohort, which includes patients presenting with cognitive complaints at the Cognitive Decline and Movement Disorders Unit of Hospital del Mar (Barcelona, Spain). Patients were classified into an AD CSF profile group or a non‐AD CSF profile group according to their CSF Aβ42/P‐tau181 ratio (Lumipulse, Fujirebio), and the discrimination accuracy of 9 plasma Tau assays was tested. All plasma samples were treated identically and measurements were performed in a blinded fashion. Result: A total of 197 participants (109 women [55.3%]; mean [SD] age, 72.3 [5.83] years), were investigated. All plasma Tau biomarkers were significantly higher in the AD CSF profile group than in the non‐AD CSF profile group. For plasma Tau biomarkers, the largest effect sizes were found in plasma Janssen P‐tau217 (r = 0.76), Lilly P‐tau217 (r = 0.73), ADx P‐tau181 (r = 0.73), Lilly P‐tau181 (r = 0.68), and UGot P‐tau231 (r = 0.63). All plasma Tau biomarkers significantly discriminated between patients with an AD CSF profile group from those with a non‐AD CSF profile. The AUC of plasma Tau biomarkers were the following (from highest to lower): Janssen P‐tau217 (0.96; 95% CI, 0.93‐0.99), ADx P‐tau181 (0.94; 95% CI, 0.91‐0.97) and Lilly P‐tau217 (0.94; 95% CI, 0.90‐0.98), Lilly P‐tau181 (0.91; 95% CI, 0.87‐0.96), UGot P‐tau231 (0.88; 95% CI, 0.83‐0.93), Quanterix P‐tau181 (0.80; 95% CI, 0.73‐0.87), UGot P‐tau181 (0.80; 95% CI, 0.73‐0.87), Lilly Total‐tau (0.73; 95% CI, 0.65‐0.81), and ADx P‐tau231 (0.66; 95% CI, 0.58‐0.74). Conclusion: The findings indicate that there are several plasma P‐tau biomarkers that can be used in a memory clinic setting as a stand‐alone biomarker to detect AD pathology in a diverse group of patients presenting with cognitive complaints.